Surface‐treated kaolin minerals as a complement or substitute to glass fibers in thermoplastics. (25th October 2018) - Baioumy, Mohamed Gamal Shafik; Colton, Jonathan; Poulakis, John; Kalaitzidou, Kyriaki
Abstract : Glass fiber (GF)‐related mold abrasion and tool wear make it undesirable for certain thermoplastics applications. Furthermore, fiber attrition during processing and orientation sensitivity raise concerns over compromised performance. In this study, kaolin minerals with varying properties and surface‐treatments are tested to potentially replace GFs in nylon composites. Composites are melt‐compounded and injection molded using lab‐scale and industrial‐scale equipment. Mechanical properties (tensile, flex, impact), heat distortion temperature, and thermal decomposition using thermogravimetric analysis (TGA) are used to comparatively characterize kaolin composite formulations against 30% weight GF composites. Kaolin minerals with high aspect ratio and good interfacial contact are found to show strength and modulus improvements up to 80% that of GF. Additionally, low aspect ratio kaolin composites were found to surpass GF composites in impact strength. A synergistic effect is found between high and low aspect ratio kaolin that can potentially lead to further enhancement in properties with the added possibility of blending minerals to customize composite performance. Such findings suggest that kaolin minerals can be used to customize the properties of composites in manners previously unattainable through GF usage alone. Scale up trials show potential for kaolin to replace GFs at industrial levels. POLYM. ENG. SCI., 59:E330–E338, 2019. © 2018 Society of Plastics Engineers